Comparative genomics of the NKG2D ligand gene family. Issue 1 (September 2015) - Kasahara, Masanori; Sutoh, Yoichi
Summary: NKG2D ligands (NKG2DLs) are a group of stress‐inducible major histocompatibility complex (MHC) class I‐like molecules that act as a danger signal alerting the immune system to the presence of abnormal cells. In mammals, two families of NKG2DL genes have been identified: the MIC gene family encoded in the MHC region and the ULBP gene family encoded outside the MHC region in most species. Some mammals have a third family of NKG2DL‐like class I genes which we named MILL (MHC class I‐like located near the leukocyte receptor complex). Despite the fact that MILL genes are more closely related to MIC genes than ULBP genes are to MIC genes, MILL molecules do not function as NKG2DLs, and their function remains unknown. With the progress of mammalian genome projects, information on the MIC, ULBP, and MILL gene families became available in many mammalian species. Here, we summarize such information and discuss the origin and evolution of the NKG2DL gene family from the viewpoint of host–pathogen coevolution.